Divisia and Simple Sum Monetary Aggregates: Any Empirical Relevance for Turkey? - POLAT, UMURCAN (DE GRUYTER POLAND SP ZOO, 2018)
In consideration of channels through which monetary policy affects economic activity, the monetary aggregates have been mostly ignored by the monetary authorities instead of which short-run interest rates have been given a priori role. These monetary aggregates are largely argued to fail in measuring the effectiveness of different monetary policy regimes in forecasting the macroeconomic fundamentals. Grounded on the Barnett critique, the formation of traditional simple-sum monetary aggregates assuming for perfect substitution among the components of the money supply is blamed for such a failure of money in explaining the real activity. Given increasing varieties of financial assets which have completely different moneyness, it is important to provide an alternative measure of the money supply. Hereby, the Divisia monetary aggregates which give different weights to different assets have arisen as an alternative approach. In this study, a Divisia index is constructed to test its predictive power on quantities and prices compared to its simple sum counterpart. Accordingly, a Divisia index is built-up for Turkish economy for the period 2006-2016 to see whether the utilization of the Divisia monetary aggregates in the conduct of monetary policy makes any difference compared to that of traditional simple sum money supply. Under different specifications, though the relative power of the Divisia aggregates in predicting quantity and price variables is found, still, it can be argued that theoretically well-rounded formation of the Divisia index is not that much empirically justified for the case of Turkey.
Keywords: Turkey; Monetary policy; Monetary aggregation; Divisia index; Simple sum index